VAL-U: Psychometric properties of a Values and Civic Attitudes Scale for University Students’ Service-Learning - Ruiz-Ordóñez,Yolanda (2022)
Abstract The service-learning disciplines can offer a unique opportunity for civic development in university students, as there is a large body of research that links it to values and civic attitudes including a vast number of ecological issues and citizen variables. Moreover, one should bear in mind that these students are future generations that will face many pressing social and environmental issues. Given the need to develop instruments to measure the impact of a service-learning methodology in university students’ values as well as civic attitudes, VAL-U is proposed. As the university can be considered a learning step prior to the professional field, the main objective of this study was to analyse the internal consistency and factor structure of the proposed VAL-U scale in the Spanish population. The scale confirmed acceptable psychometric properties. Furthermore, the results have shown high reliability and optimal goodness of fit. Promising results are offered to employ VAL-U as a valuable tool for assessing Values and Civic Attitudes Scale for Spanish-speaking University Students’ Service-Learning.